Analisis Manfaat Susu Kambing Berdasarkan Hadis dan Relevansinya dengan Kesehatan Modern: Studi Kasus Desa Kedai Durian Deli Tua Deli Serdang - Sarah Putri Wijaya; Muhammad Jamil (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
This study explores the health benefits of goat milk as referenced in Hadith, using Kedai Durian Village in the Deli Tua District as a case study. Employing a qualitative research design, data were collected through in-depth interviews with members of the local community and a comprehensive literature review of Hadith texts pertaining to goat milk. The findings indicate that goat milk contributes positively to human health by enhancing immune function, supporting digestive health, and promoting nutritional balance. Furthermore, residents of Kedai Durian Village who regularly consume goat milk demonstrated a growing awareness of the importance of aligning dietary practices with Islamic teachings. Notably, improvements in health outcomes were observed, with cases of dengue fever (DBD), tuberculosis (TB), gastric ulcers, and high fever reportedly responding positively to the routine intake of goat milk. Based on these findings, the study recommends the broader promotion of goat milk consumption as a means to support public health in accordance with Islamic dietary principles.